Myths and Realities of Aging - Carolyn S. Wilken (EDIS, 2003)
This fact sheet describes some of the prejudices our society has about aging. Ten of the most common myths of aging are explored. A description of what is really true follows each myth. This document is FCS2193, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida: First published: June 1989. Reviewed: August 1999, March 2002. Revised: December 2002.